The
correct answer is:
D)
![\left \{ {{2x-y=7} \atop {2x+7y=31}} \right.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/cjb4bafn3qc3tcymn0u7jumxao8qv1fpkd.png)
.
Step-by-step explanation:
We solve each system to find the correct answer.
For A:![\left \{ {{3x-2y=9} \atop {3x+2y=14}} \right.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/fjmwvah72pnzzhz4sus9abzjppf00tynwv.png)
Since we have the coefficients of both variables the same, we will use
elimination to solve this.
Since the coefficients of y are -2 and 2, we can add the equations to solve, since -2+2=0 and cancels the y variable:
![\left \{ {{3x-2y=9} \atop {+(3x+2y=14)}} \right. \\ \\6x=23](https://img.qammunity.org/2019/formulas/mathematics/middle-school/q5ab09qziy71tjv78hiuizctzcxnykwq65.png)
Next we divide both sides by 6:
6x/6 = 23/6
x = 23/6
This is
not the x-coordinate of the answer we are looking for, so
A is not correct.
For B:
![\left \{ {{x-y=-2} \atop {4x-3y=11}} \right.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tl258ez9t4ya8rfrauolkb5y0a8z3a5hzb.png)
For this equation, it will be easier to isolate a variable and use
substitution, since the coefficient of both x and y in the first equation is 1:
x-y=-2
Add y to both sides:
x-y+y=-2+y
x=-2+y
We now substitute this in place of x in the second equation:
4x-3y=11
4(-2+y)-3y=11
Using the distributive property, we have:
4(-2)+4(y)-3y=11
-8+4y-3y=11
Combining like terms, we have:
-8+y=11
Add 8 to each side:
-8+y+8=11+8
y=19
This is
not the y-coordinate of the answer we're looking for, so
B is not correct.
For C:
Since the coefficient of x in the second equation is 1, we will use
substitution again.
x+2y=-11
To isolate x, subtract 2y from each side:
x+2y-2y=-11-2y
x=-11-2y
Now substitute this in place of x in the first equation:
-2x-y=-13
-2(-11-2y)-y=-13
Using the distributive property, we have:
-2(-11)-2(-2y)-y=-13
22+4y-y=-13
Combining like terms:
22+3y=-13
Subtract 22 from each side:
22+3y-22=-13-22
3y=-35
Divide both sides by 3:
3y/3 = -35/3
y = -35/3
This is
not the y-coordinate of the answer we're looking for, so
C is not correct.
For D:
Since the coefficients of x are the same in each equation, we will use
elimination. We have 2x in each equation; to eliminate this, we will subtract, since 2x-2x=0:
![\left \{ {{2x-y=7} \atop {-(2x+7y=31)}} \right. \\ \\-8y=-24](https://img.qammunity.org/2019/formulas/mathematics/middle-school/7b5f3qse0viw1n1vt9whtpvkefkczbg1nj.png)
Divide both sides by -8:
-8y/-8 = -24/-8
y=3
The y-coordinate is correct; next we check the x-coordinate Substitute the value for y into the first equation:
2x-y=7
2x-3=7
Add 3 to each side:
2x-3+3=7+3
2x=10
Divide each side by 2:
2x/2=10/2
x=5
This gives us the x- and y-coordinate we need, so
D is the correct answer.